Impact Of Cervical Stabilisation Exercises On Posture Ailment In Text Neck Syndrome - Baranwal, Shashank; Saharan, Ajeet Kumar; Sharma, Shantanu; Choudhary, Anuja; Saini, Hari Narayan; Singh, Shashank Shekhar; Vanshika, Vanshika (Journal of Neonatal Surgery, 2025)
Background: The solubilization of poorly soluble drugs belonging to Class II of the Biopharmaceutical Classification Background: Text neck syndrome, also known as forward head posture (FHP), has emerged as a common musculoskeletal disorder among smartphone users. Global prevalence ranges from 32% to 68.1%, with particularly high rates among university and medical students. This condition leads to altered cervical biomechanics, reduced craniovertebral angle (CVA), neck pain, and functional limitations. Objective: To evaluate the effectiveness of cervical stabilization exercises in correcting forward head posture associated with smartphone use. Methods: Evidence from clinical trials and systematic reviews was analyzed. Outcomes included changes in CVA, pain reduction measured by the Visual Analog Scale (VAS), and functional improvement using the Neck Disability Index (NDI). Interventions reviewed encompassed deep cervical flexor training, pressure biofeedback, scapular stabilization, and McKenzie-based protocols. Results: Cervical stabilization programs consistently improved CVA by 6–10° and reduced pain scores by 2.5–4.5 points on the VAS within 4–8 weeks. Combined exercise protocols that integrated postural education, flexor strengthening, and functional retraining produced the most favorable results, with nearly 50% of patients shifting from moderate–severe to mild disability levels. Conclusion: Cervical stabilization exercises represent an effective, evidence-based intervention for managing smartphone-related forward head posture. Their systematic implementation can significantly reduce pain and improve functional outcomes.